Conventional polymerase chain reaction (PCR) assay for detection and characterization of bacterial leaf blight in wheat applied by ICARDA’s GHU - Kumari, Safaa; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2022)
Wheat is one of the most important crops for global food security and represents a main source of food and income for millions of smallholder farmers worldwide. Pseudomonas syringae pv. syringae (Pss) is the causal agent of bacterial leaf blight or leaf necrosis disease with specific symptoms on wheat leaves and spikes and in good conditions it can reach to the seeds to be seed borne disease. Yield losses caused by Pss can reach up to 50% or more depending on the crop, time of infection, and region. Therefore, developing and implementing effective management strategies for bacterial diseases is very important to reduce yield and quality loss. However, accurate detection of diseases is the first essential step for effective management strategies for control of this disease. Molecular is efficient tool to accurately detect and monitor the occurrence and development of crop diseases. This report describes a validated conventional polymerase chain reaction (PCR) assay for Pss detection and characterization applied by ICARDA’s GHU.